Percepatan NIB (Nomor Induk Berusaha) Wonogiri Melibatkan Ikatan Mahasiswa Berprestasi (IMAPRES) - Muddatsir, Nani Alia; Setianingsih, Endang Larasati; Yuniningsih, Tri (Universitas Medan Area, 2024)
The legality of business permits is important in developing Micro, Small and Medium Enterprises (MSMEs). NIB or Business Identification Number is an identity number used by business actors to obtain business permits and commercial or operational permits. Online Single Submission (OSS) is an Electronically Integrated Business Permit application issued by the OSS institution on behalf of the Minister, Agency Head, Governor, or Regent/Mayor to business actors via electronic means integrated by the system. IMAPRES, or the Association of Achievement Students in Wonogiri Regency, is a student organization that receives scholarships in Wonogiri Regency. The goal to be achieved in the Business Identification Number or NIB acceleration program is that the Wonogiri Regency is required to complete the NIB or Business Identification Number from 294 villages. The method used uses stages such as observation or survey, counseling regarding Business Identification Numbers or NIBs, and implementation of assistance and creation of NIBs or Business Identification Numbers. The Department of Investment and One Stop Integrated Services (DPMPTSP) is collaborating with IMAPRES or the Association of Achievement Students in Wonogiri Regency to complete the NIB (Business Identification Number).